2016
DOI: 10.1155/2016/2143082
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Conbercept Injection with and without Grid Laser Photocoagulation in the Treatment of Diffuse Diabetic Macular Edema in Real-Life Clinical Practice

Abstract: Purpose. To evaluate the efficacy of intravitreal conbercept (IVC) plus modified grid laser photocoagulation (MGP) versus IVC alone for treatment of diffuse diabetic macular edema (DDME). Methods. In this retrospective study, 51 DDME patients were treated with either IVC alone (IVC group) or IVC plus MGP (combined group) with 12 months of follow-up. The clinical records of those patients were reviewed. Results. 26 patients (31 eyes) received IVC alone and 25 patients (30 eyes) received combined therapy. At mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Even though the structural and functional merits of conbercept have been demonstrated in laboratories and it has been shown to be more cost-effective than ranibizumab in a small-sized clinical study,69 its therapeutic equivalency or superiority to VEGF mAbs has not been demonstrated in large-scale clinical trials. Furthermore, a small-sized clinical trial conducted in People’s Republic of China has compared the efficacy of the therapeutic modality combining laser with IVC with that of IVC alone 53. The results suggest that the combinatorial therapy may be a promising modality for DME due to its cost-effectiveness and reduced risk of adverse events, while maintaining equal efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the structural and functional merits of conbercept have been demonstrated in laboratories and it has been shown to be more cost-effective than ranibizumab in a small-sized clinical study,69 its therapeutic equivalency or superiority to VEGF mAbs has not been demonstrated in large-scale clinical trials. Furthermore, a small-sized clinical trial conducted in People’s Republic of China has compared the efficacy of the therapeutic modality combining laser with IVC with that of IVC alone 53. The results suggest that the combinatorial therapy may be a promising modality for DME due to its cost-effectiveness and reduced risk of adverse events, while maintaining equal efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few clinical trials studying the therapeutic efficacy of combining conbercept with laser therapy have been reported. A retrospective study involving 51 patients was conducted in 2016 to compare the efficacy of IVC plus grid laser photocoagulation (GLP) with IVC alone in the treatment of diffuse DME 53. At 12 months after therapy, the mean BCVA improved 9.1±4.5 letter score in the IVC group and 7.5±4.2 letter score in the combination group.…”
Section: Clinical Trailsmentioning
confidence: 99%
“…271 Novel anti-VEGF therapies that may be more effective, durable and cheaper than current agents such as conbercept are currently in trial for DME. 272 Other agents involving combination therapy, such as Genentech's anti-VEGF/ANG-2 (RG7716), have yielded favorable efficacy and durability data in recent Phase II studies. 273 In addition, optimal strategies for combining anti-VEGF and corticosteroid treatment are still undergoing investigation despite the recent marginal results provided by protocol U of the DRCR network.…”
Section: Future Trends Diagnosticsmentioning
confidence: 99%
“…us, therapeutic approach by inhibiting VEGF may be provided as an effective treatment of DME. Intravitreal anti-VEGF agents could significantly improve the vision and anatomic outcomes in DME patients, and their long-term efficacy and safety have been proven in numerous randomised trials [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%